AB0059 Synovial secretion of pro-inflammatory and pro-oxidant molecules triggered by monosodium urate crystals induces ngf and h2o2 pain mediators in the chondrocyte. (15th June 2017) - Lopez-Reyes, AG; Medina-Luna, D; Satamaria-Olmedo, M; Martinez-Flores, K; Zamudio-Cuevas, Y; Fernandez-Torres, J; Martinez-Nava, G; Clavijo-Cornejo, D; Olivos-Meza, A; Gutierrez, M; Fernandez-Moreno, M; Blanco, F; et al.
Abstract : Background: Gout is the most prevalent inflammatory arthropathy in young men, in which clinical manifestations are triggered by the deposits of monosodium urate (MSU) crystals in and around joints. From a clinical perspective, gouty attacks and tophaceous deposits have been associated to nodal osteoarthritis [1, 2]. Objectives: To determine the molecular mechanisms associating MSU crystal deposits with chondrocyte activation and changes in articular cartilage. Methods: Primary cultures of synoviocytes were activated with MSU crystals for 24 h, the resulting supernatant was used as a supplementary conditioning basal medium (CBM) for 24 h chondrocyte growth. The expression level profile of cytokines (IL-6, IL-8) and nerve growth factor (NGF) in the supernatant was measured. Production of reactive oxygen and nitrogen species, such as O2 ●, H2 O2, and NO ●, was also measured intracellularly. Results: Upon activation by MSU crystals, synoviocytes increased secretion of IL-6 and IL-8, as well as intracellular production of O2 ●, H2 O2, and NO ● in comparison to non-stimulated synoviocytes. Additionally, the chondrocytes incubated with CBM for 24 h increased significantly IL-6, IL-8, and NGF levels, as well as O2 ●, H2 O2, and NO ● levels when compared to non-stimulated chondrocytes. Secretion of these soluble mediators was even higher than the one observed in the synoviocytes and chondrocytes directly stimulated with MSU crystals. Conclusions: Pro-inflammatory cytokine secretion induced by MSU crystals in synoviocytes triggers chondrocyte activation, intensifying the articular inflammatory state in gouty attacks. Furthermore, the increase in reactive species (particularly NO ●, which inhibits proteoglycan synthesis) compromises the homeostasis of the extracellular matrix of the cartilage. Finally, overproduction of NGF and H2 O2 by the chondrocyte functions a pain modulator during gout attacks. References: Fam AG, et al. Gouty arthritis in nodal osteoarthritis. J Rheumatol 1996; 23:684–9. Roddy E, et al. Gout and nodal osteoarthritis: a case-control study. Rheumatology (Oxford) 2008; 47:732–3. Disclosure of Interest: None declared